The Influence of Motivation, Discipline, and Job Satisfaction on Employee Performance at UD. Hikmat Sejahtera - Ageng Febrianti; April Liyana Ningsih; Dharliana Hardjowikarto (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine the role of motivation, work discipline, and jobsatisfaction in predicting employee performance at UD Kebijaksana Kemakmuran, Cirebon, West Java. The population in this study was all employees of UD Kebijaksana Kemakmuran. The sampling technique used was saturated sampling, with all employees being sampled, resulting in a total of 50 respondents. Data collection was conducted through a survey using a questionnaire. The data analysis technique used in this study was multiple linear regression. The results showed that the three independent variables, namely motivation, work discipline, and job satisfaction, had a positive and significant effect on employee performance, both partially and simultaneously. This study also discusses the meaning of these findings, which are presented at the end of the paper.